Risk Analysis and Mitigation of Occupational Safety Accidents in the Maintenance Process of Units - Adnyani, Luh Putri; Rimeily; Putri, Destyariani Liana; Nurmawati; Wirawan, Muhammad Khaisar (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
The maintenance process involves the use of various equipment, machinery, and workspaces, all of which inherently present occupational hazards. If these risks are not adequately addressed, they may lead to workplace accidents. Ensuring worker protection remains a critical concern due to the persistent occurrence of occupational incidents and the presence of workplace hazards that pose significant risks to employees. Therefore, this study aims to identify and assess occupational accident risks during unit maintenance, develop strategies to mitigate these risks, and enhance occupational safety and health (OSH) practices at company. This study identified 27 potential workplace accidents arising from six major hazard categories. These hazards were incorporated into a structured questionnaire, which was then distributed to relevant workers to gather empirical data. The collected responses were analyzed and systematically classified using a risk matrix framework, categorizing risks from low to high levels to prioritize appropriate mitigation measures. The risk assessment identified several high-risk incidents, particularly those categorized under accident codes A1, A3, B3, B4, B5, C3, C4, D1, D5, E1, E2, E3, E4, and E5. Following the risk assessment, targeted mitigation strategies were implemented to address workplace hazards across various job functions. These measures included the mandatory use of personal protective equipment (PPE) tailored to specific tasks, alongside strict adherence to established safety protocols and warning systems to prevent occupational accidents. The findings highlight the necessity for continuous safety monitoring, employee training, and a proactive risk management approach to ensure a safer working environment.